Protesto de certidão de dívida ativa: extrajudicialização da cobrança de créditos fiscais como mecanismo de acesso à justiça - Murad, Flavia Santos (2015)
This dissertation aimed to research a mechanism that would allow better access to the courts of justice for tax credit recovery, using a faster and more efficient way than the existing legal system in current form. This scientific study tried to answer the following question: extrajudicial protest regarding the certificate of outstanding debt can be used as a means of access to the courts, seeking greater celerity and effectiveness in satisfying tax credit? To answer this question, we used the dialectical method, through exploratory and bibliographic research. The first chapter discusses the fundamental right of access to justice. It contextualizes the guarantees of the right of effectiveness and procedural celerity. Subsequently, the chapter discusses the crisis of Judiciary in a democratic rule of law. It also observes the universal movement of justice access and if extra legalization can be understood as such a mechanism of courts access. The second chapter explains what are the outstanding debt and the composition of the certificate of outstanding debt. It also examines the process of tax enforcement and the crisis in which it finds itself actually. In addition, the chapter discusses the possibility of using extra-legalization for tax claims recovery. It would be an alternative way to tax credits collection in a more effective manner, explaining on the doctrinal divergence as the use of extrajudicial protest procedure on certificate of outstanding debt. The last chapter analyzes extrajudicial protest of outstanding debt certificate as a mechanism used for the collection of tax credit. It also explain the relevance with respect to the celerity and effectiveness in the implementation of extrajudicial procedure. The chapter makes a comparison between the process of tax enforcement, which is the traditional way of collecting tax credit, and the procedure of extrajudicial protest certificate of outstanding debt. All this relates to the effectiveness of these collecting mechanisms, contemplating the cost, time and the percentage of collection of both procedures. Finally, it notes that the form of extra-legalization of tax claims recovery using extra-judicial protest certificate of outstanding debt has greater effectiveness ensuring access to fair legal order, seeking a social Justice.